" المناسبة بين الكفاءة الأساسية بمحتوى الكتاب المدرسي"دروس اللغة العربية - Nur Hidayah, Arini Ulfa; Muslim, Buhori; Muzaffar, Asyraf (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
The subject of this thesis is “The Compatibility between Basic Competencies and the Contents of the Book "Arabic Lessons"”. One of the reasons that led the researcher to write this thesis because the teacher uses this book as one of the learning media. Hypothetically, the contents of the book "Arabic Lesson, Student Book (Curriculum Scientific Approach 2013) for MA Class X" are not in line with the basic competencies that have been summarized by the government. Therefore, the researcher wanted to do this research to find out the extent of conformity and nonconformity between basic competence with the content of the book "Arabic Lesson". The objectives of this thesis are to identify the suitability between the basic competencies of the curriculum 2013 for MA with the contents of the book "Arabic Lessons" and to identify the mismatch between the basic competencies of the curriculum 2013 for MA with the contents of the book "Arabic Lessons". The research method used by the researcher in writing this thesis is descriptive analysis of content analysis. The population in this study is the basic competence of the 2013 curriculum in Arabic lessons for MA as many as 96 basic competencies. In the process of collecting data, Researcher uses Document Research instrument. And using qualitative analysis in analyzing data. The results obtained by the researcher is that the contents of the book "Arabic lesson" is good and in accordance with the basic competence of the 2013 curriculum which is stated in Ministry of Manpower Decree No.165 in terms of reading, writing, listening, conversation, and sentence skills. There are some disagreements between basic competence and the hearing material in chapters 2 and 4, and the conversation material in chapter 6 as well as the sentence of  “'indi/ma'I”, the order of this sentence is found in chapter 4 in the explanation of “Jar, wa ma'naha” and there is no specific explanation about it.